Ocupações artísticas do/no espaço escolar: uma proposta de ensino e aprendizagem de teatro no ensino médio - Daniela Moreno de Camargo (2023)
This article presents the results of a master's research aimed at developing a pedagogical proposal from the perspective of artistic creation and the occupation of school space. The discussion revolves around possibilities for teaching and learning Art, especially theater, in high school, focusing on students' autonomy and protagonism in basic education. The study examines the relationship between artistic creation and critical reflection on the world, the use and occupation of school spaces as environments for theater creation and experimentation, as well as students' active participation in knowledge construction. The proposed methodology is qualitative and exploratory, involving reference research, document analysis, and adopting the approach of Arts-Based Educational Research (ABER), particularly A/R/Tography (Oliveira; Charreu, 2016), for the development of the theater teaching and learning project integrated into the research. In the critical interpretative discussion, the study draws on ideas of Pedagogy of Autonomy and Education for Freedom by Paulo Freire (2013), the discussion on the relationship between education and youth by Juarez Dayrell (1996), and post-dramatic theater in schools by Carminda Mendes André (2011), among other relevant authors in the fields of Theater and education. Ultimately, the research points to possibilities for creating repertoires, narratives, and meanings for teaching and learning Art - Theater, based on students' autonomy and protagonism in basic education.